2004
DOI: 10.1152/physiolgenomics.00227.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an angiotensin-(1–7)-producing fusion protein produces cardioprotective effects in rats

Abstract: Angiotensin-(1-7) [ANG-(1-7)] is a recently described heptapeptide product of the renin-angiotensin system. Because biosynthesis of ANG-(1-7) increases in animals treated with cardioprotective drugs and inactivation of the gene for angiotensin converting enzyme 2 [an enzyme involved in the biosynthesis of ANG-(1-7)] leads to the development of cardiac dysfunction, it has been suggested that ANG-(1-7) has cardioprotective properties. To directly test this possibility, we have generated transgenic rats that chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
164
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 38 publications
(57 reference statements)
16
164
1
2
Order By: Relevance
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…In contrast to the present study, Ferreira et al showed an improved cardiac function, indicated by elevated dp/dt anddp/dt and furthermore, an attenuation of the isoproterenolinduced cardiac fibrosis in transgenic rats. Previous studies also indicated an antifibrotic action of Ang(1-7) in vitro and in vivo (Santos et al, 2004;Ferreira et al, 2010;Dong et al, 2012;McCollum et al, 2012;Acuña et al, 2014). In contrast to these findings, the present study revealed no antifibrotic effect of Ang(1-7) in a transgenic rat model.…”
Section: Discussioncontrasting
confidence: 88%
“…Thus, the findings of Ferreira et al seemed to be due to local production of cardiac Ang(1-7), whereas our results were rather caused by systemic alterations. Santos et al (2004) measured Ang(1-7) in the same model as we used, demonstrating elevated Ang(1-7) plasma concentration, but unaltered tissue levels, which may be a result of the short half-life of Ang(1-7), which is about 10 s (Yamada et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, we could speculate that, part of this antiarrhythmogenic property of losartan could be mediated by an interaction with Ang-(1-7) receptors. This seems to be an interesting possibility, since cardioprotective effects were recently described for Ang-(1-7) (Santos et al, 2004). Clearly, future studies are necessary to unravel the mechanism and other consequences involved in the interaction between losartan and Ang-(1-7) receptors on the cardiac function.…”
Section: Discussionmentioning
confidence: 94%